2019
DOI: 10.1387/ijdb.180414ap
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the mouse: non-rodent animal models for study of early mammalian development and biomedical research

Abstract: The preimplantation development of mammals generally follows the same plan. It starts with the formation of a totipotent zygote, and through consecutive cleavage divisions and differentiation events leads to blastocyst formation. However, the intervening events may differ between species. The regulation of these processes has been extensively studied in the mouse, which displays some unique features among eutherian mammals. Farm animals such as pigs, cattle, sheep and rabbits share several similarities with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 213 publications
0
25
0
Order By: Relevance
“…Previous studies have suggested that pigs are a valuable biomedical model based the similarly genomic and physiological features to humans (Groenen et al, 2012; Madeja et al, 2019), and much evidence has indicated that pigs have been widely used as animal model in studies associated MI (Gabisonia et al, 2019; Lopez et al, 2019). In this study, the potential miRNAs that might involve in the processes of cardiac fibrosis after MI were identified in the miniature pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that pigs are a valuable biomedical model based the similarly genomic and physiological features to humans (Groenen et al, 2012; Madeja et al, 2019), and much evidence has indicated that pigs have been widely used as animal model in studies associated MI (Gabisonia et al, 2019; Lopez et al, 2019). In this study, the potential miRNAs that might involve in the processes of cardiac fibrosis after MI were identified in the miniature pigs.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reasons for the slow progress such as rare occurrence, molecular complexity, and variability of symptoms. However, a decisive factor is the availability, quality, and use of experimental models [4][5][6][7][8][9][10][11][12][13]. NPC is a prime example for a disease that lacks a curative therapy despite impressive breakthroughs within the last decades [14][15][16][17] and rapidly growing publication counts (Appendix A, Figure 1).…”
Section: Niemann-pick Type C Diseasementioning
confidence: 99%
“…Where the mouse shows unique regulatory mechanisms, other animals share great similarities in their developmental plan. The moment of zygotic genome activation, the first lineage differentiations and maintenance of pluripotency are some aspects that are not always conserved between species, but are very similar in cows and pigs compared to humans (reviewed in [ 1 , 2 , 3 ]). Furthermore, the scarcity of human embryos and the ethical and logistical challenges increase the need to work with other models.…”
Section: Introductionmentioning
confidence: 99%